The Influence of Workload and Environment on Turnover Intention Through Job Satisfaction and Organizational Commitment - Didik Hariyanto; Budi Eko Soetjipto; Sopiah Sopiah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This research aims to analyze the effect of workload and work environment on turnover intention through job satisfaction and organizational commitment. The research sample was 175 employees who were taken by proportional random sampling. Data analysis using Partial Least Square (PLS). The research findings show that workload has a significant positive effect on job satisfaction, organizational commitment, and turnover intention directly. The work environment significantly negatively affects turnover intention, while job satisfaction and organizational commitment have a significant positive effect. Job satisfaction significantly negatively affects turnover intention, while organizational commitment has a significant positive effect. Organizational commitment has a significant negative effect on turnover intention. Indirectly, the workload negatively affects turnover intention through job satisfaction and organizational commitment. The work environment has a significant negative effect on turnover intention through job satisfaction and organizational commitment, and job satisfaction has a significant negative effect on turnover intention through organizational commitment.